(untitled) (Eurasian Journal of Philology Science and Education, 2018)
This article raises issues about globalization of financial and economic markets of major countries and the predominant role of English-speaking countries in shaping the direction and development of financial and economic processes. The article considers a financial analytical discourse as a special type of financial and economic discourse and its meta language. Special attention is given to the central role of the conceptual metaphor in conceptualization and categorisation of this discourse. Within the framework of this discourse conceptual metaphors shape conceptual models that facilitate the perception of information transferred through media texts. The model «Financial Market as a Body of Water» is analysed in terms of intercultural communication based on similarities and differences of English and Russian media texts at cognitive and linguistic levelsand is translated into the target language via various translation techniques. Thisarticlecouldbeusefultolinguists, translatorsaswellasspecialists in economics.